2015
DOI: 10.1177/2325967115605801
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Rotator Cuff Repair Using the Undersurface Technique

Abstract: Background:Arthroscopic rotator cuff repair has traditionally been performed in the subacromial space from the bursal side of the tendon. The undersurface rotator cuff repair technique involves the arthroscope remaining in the glenohumeral joint, thus viewing the tendon from its undersurface during repair without a bursectomy or acromioplasty.Purpose:To compare the clinical and structural outcomes of undersurface rotator cuff repair with bursal-side repair.Study Design:Cohort study; Level of evidence, 3.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
0
12
1
Order By: Relevance
“…Previous studies have shown that undersurface repairs were, on average, between 12 and 32 minutes faster to perform than bursal-sided repairs when the same suture anchors were used. 23,29 The difference in operative time is most likely because there is no need to perform a bursectomy or acromioplasty. Furthermore, performing an acromioplasty and/or bursectomy may induce bleeding, which can impair visualization of the torn tendon and other structures within the glenohumeral joint.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that undersurface repairs were, on average, between 12 and 32 minutes faster to perform than bursal-sided repairs when the same suture anchors were used. 23,29 The difference in operative time is most likely because there is no need to perform a bursectomy or acromioplasty. Furthermore, performing an acromioplasty and/or bursectomy may induce bleeding, which can impair visualization of the torn tendon and other structures within the glenohumeral joint.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, performing an acromioplasty and/or bursectomy may induce bleeding, which can impair visualization of the torn tendon and other structures within the glenohumeral joint. 23,29…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Before repair debridement of the torn tendon and anatomical footprint was completed using an arthroscopic shaver. The tear was repaired using either a bursal or an undersurface approach as outlined by Rubenis et al 31 . Sutures were passed through the torn tendon using the Opus Smart Stitch device (ArthroCare Corp, Sydney, Australia).…”
Section: Methodsmentioning
confidence: 99%